Congenital Hypothyroidism in Preterm Newborns – The Challenges of Diagnostics and Treatment: A Review - Klosinska, Martyna; Kaczynska, Agnieszka; Ben-Skowronek, Iwona (Frontiers in Endocrinology, 2022)
Preterm newborns are forced to adapt to harsh extrauterine conditions and endure numerous adversities despite their incomplete growth and maturity. The inadequate thyroid hormones secretion as well as the impaired regulation of hypothalamus-pituitary-thyroid axis may lead to hypothyroxinemia. Two first weeks after birth are pivotal for brain neurons development, synaptogenesis and gliogenesis. The decreased level of thyroxin regardless of cause may lead to delayed mental development. The disorder originates from maternal factors, perinatal and labor complications, genetic abnormalities, thyroid malformations as well as side effects of medications and therapeutic actions. Because of that, the prevention is not fully attainable. CH manifests clinically in a few distinctive forms: primary, permanent or transient, and secondary. Their etiologies and implications bear little resemblance. Therefore, the exact diagnosis and differentiation between the subtypes of CH are crucial in order to plan an effective treatment. Hypothyroxinemia of prematurity indicates dynamic changes in thyroid hormone levels dependent on neonatal postmenstrual age, which directly affects patient’s maintenance and wellbeing. The basis of a successful treatment relies on an early and accurate diagnosis. Neonatal screening is a recommended method of detecting CH in preterm newborns. The preferred approach involves testing serum TSH and fT4 concentrations and assessing their levels according to the cut-off values. The possible benefits also include the evaluation of CH subtype. Nevertheless, the reference range of thyroid hormones varies all around the world and impedes the introduction of universal testing recommendations. Current guidelines recommend levothyroxine treatment of CH in preterm infants. The two first weeks of life are the “therapeutic window” for improvement of premature newborn mental and motor development by an adequate therapy. However, results from multiple clinical trials are mixed and depend on the newborn’s gestational age at birth. Some benefits of treatment are seen especially in the preterm infants born <29 weeks’ gestation. The discrepancies among trials create an urgent need to conduct more large sample size studies that could provide further analyses and consensus. This review summarizes the current state of knowledge on congenital hypothyroidism in preterm infants. We discuss screening and treatment options and demonstrate present challenges and controversies.